EVALUATION OF THE COMPRESSIVE STRENGTH OF ICE UNDER SHORT-TERM RAPIDLY INCREASING LOAD - Korzhavin,K. N.; Ptukhin,F. I. (1969)
A mathematical analysis of the strength of ice, as a component of frozen rock or soil. Strengths are differentiated for compressive and shear loading at various rates over various periods of time. (Author) Trans. of mono. Vsesoyuznaya Mezhduvedomstvennaya Soveshchaniya po Geokriologii (Merzlotovedemiyu) (8th). Materialy, v5, n.p., 1966 p61-72.